2020
DOI: 10.1177/0886260520967746
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Parental Aggression and the Development of Psychopathology in Young Children: The Mediating Role of Early Dissociative Symptoms

Abstract: Exposure to child-directed parental aggression in early life has been found to increase the risk of later psychopathological symptoms among children and adolescents. However, little is known about intermediate phenotypes and the developmental progression of symptoms, especially across the transition to grade school. Using prospectively collected longitudinal data from a large sample of children enrolled in the Family Life Project ( n = 1,166, 49.7% female), the current study examined the mediating role of earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Contrary to the results of Zhang et al . 19 , where females showed higher levels of ADSs scores than males. However, these differences could be attributed to the difference in the sociocultural context (China–Europe), as well as the context of the COVID-19.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Contrary to the results of Zhang et al . 19 , where females showed higher levels of ADSs scores than males. However, these differences could be attributed to the difference in the sociocultural context (China–Europe), as well as the context of the COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…There is an urgent need for scientifically proven and improved potentially modifiable impact factors associated with ADD during the COVID-19 pandemic. Some studies suggested that a modifiable impact factors associated with ADD, such as DSs, should be raised 18 , 19 . According to the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5), DSs refer to abnormal integration of thoughts, feelings, and experiences (e.g., disengagement, memory disturbances, derealization, and identity alteration) in the stream of consciousness and memory 20 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations